Design, Synthesis, and Biological Evaluation of N-Acyl-Homoserine Lactone Analogs of Quorum Sensing in Pseudomonas aeruginosa - Wei, Zhenyu; Li, Ting; Gu, Yan; Zhang, Qian; Wang, Enhui; Li, Wenbo; Wang, Xin; Li, Yang; Li, Hongyu (Frontiers in Chemistry, 2022)
Quorum-sensing plays an essential role to orchestrates virulence factors and biofilm production on opportunistic multidrug resistance pathogen Pseudomonas aeruginosa. Thus, the development of inhibition of Quorum-sensing is one of the most potential strategies to combat bacterial infection and antibiotic resistance. In this work, nine novel AHL-analogues were designed, synthesized and evaluated as potential quorum sensing inhibitors. The results depicted structural modifications to AHL have remarkable effects on activity. Without inhibiting growth of P. aeruginosa PAO1, 2-(4-Bromophenyl)-N-(2-Oxotetrapyri-dinefuran-3-yl) butanamide (compound NO.10) showed the excellent performance in inhibiting biofilms and virulence factors among all the compounds. In addition, compound NO.10 also exhibits the best inhibition effect on virulence production in Caenorhabditis elegans infection model. Moreover, qPCR and molecular docking further revealed that compound NO.10 was a potential quorum sensing inhibitor. In summary, NO.10 is a very promising QS inhibitor that may be useful in the treatment of P. aeruginosa infection.